La práctica docente y la inclusión de estudiantes con capacidades diferentes en el área de ciencias naturales en la carrera de educación básica de la Universidad Técnica de Cotopaxi - Reinoso Caisa, Johana Esthela (2014)
Inclusive education involves a social and cultural change and a political decision, which recognizes and accepts that we are a diverse society in which we all have the same rights and duties. Be sidsit involves understanding that inclusive education subjects those are who have been marginalized from quality of the education. Today the demands of the new school law require institutions to meet the students special abilities. The downside of all this is that very few schools in pedagogies inclusion or colleges that have the conditions for inclusion students. Urges the traing of the teachers, have therapists, rehabilitation of physical spaces in schools. But beyond all this background, the great contribution of this event is that left traces on the teachers, the desire to make a research the this topic to develop proposals that could help solve from pedagogy, teaching and learning from the point of view inclusion, without adversely affecting the learning in normal and who wish to be seen and treated as one group. Events like these are needed to be shaping the scientific community requires the education today.